Encyclopedia of African American music - Price, Emmett George; Kernodle, Tammy L., 1969-; Maxile, Horace J., Jr (ABC-CLIO, 2011)
Showcases all facets of African American music, including folk, religious, concert, and popular styles of today. Illuminates the profound role that African American music has plays in American cultural history.